Effects of monoamine oxidase inhibitors on the hypothermia produced in cats by halothane - Summers, R. J. (1969)
1. In cats, the effects of intraperitoneal injections of four monoamine oxidase (MAO) inhibitors, tranylcypromine, pheniprazine, pargyline, and nialamide, were examined on rectal temperature and on the hypothermia during anaesthesia produced by a 2 hr period of halothane inhalation. 2. A 2 hr period of halothane inhalation produced a steady fall in temperature amounting to between 2° and 3·5° C. After discontinuation of halothane inhalation, temperature quickly returned to the pre-anaesthetic level but no pyrexia developed. A peculiar stiffness of the leg muscles occurred in several experiments either at the beginning of the inhalation or after its discontinuation. 3. An injection of tranylcypromine (5 mg/kg) caused a rise in rectal temperature and prevented the hypothermia of halothane anaesthesia. This effect lasted for at least 4 hr; 20 hr after the injection, halothane again caused hypothermia. 4. An injection of pheniprazine (10 mg/kg) usually caused a small rise in temperature which was not sustained. Pheniprazine not only prevented the hypothermia of halothane anaesthesia during the subsequent 20 hr, but during the first few hours after the injection halothane inhalation actually produced a steep rise in temperature. 5. An injection of pargyline (50 mg/kg) had no effect on temperature but the hypothermia due to halothane inhalation was prevented 1 hr after the injection and attenuated after 20 hr. Injection of 200 mg/kg caused a steady rise in temperature which was accelerated when halothane was administered 1 hr later. 6. An injection of nialamide (10, 25 or 50 mg/kg) had no immediate effect on temperature, but pyrexia developed overnight after the two larger doses. The effect on the hypothermia due to halothane inhalation was greater 20 hr after the injection than it was after 1 to 2 hr. Twenty hours after injection of the two larger doses, halothane no longer produced hypothermia but caused a lethal rise in temperature either during or after its inhalation. 7. In rabbits, the effect on temperature of halothane inhalation varied. Either temperature rose slightly or it fell, but not as much as in cats. In one rabbit in which the inhalation had produced a transient rise, pyrexia developed 40 min after discontinuation of halothane.